Upregulation of microRNA‐762 suppresses the expression of GIPC3 in systemic lupus erythematosus and neuropsychiatric systemic lupus erythematosus - Jijuan Yang; Chun Li; Shuhong Chi; Hongliang Wei; Wenqing Du; Qikuan Hu (Immunity, Inflammation and Disease, 2022)
Abstract Background Systemic lupus erythematosus (SLE), especially neuropsychiatric SLE (NPSLE), is a complex systemic autoimmune disease, characterized by variable course and multiple organ dysfunction. Our study aimed to identify crucial microRNA (miRNAs) in SLE and NPSLE. Methods Totally 12 cases of serum specimens were collected from General Hospital of Ningxia Medical University (SLE = 4, NPSLE = 4, control = 4). After miRNA sequencing, differential expression analysis, miRNA target prediction, and miRNA‐messenger RNA (mRNA) regulatory network construction were performed to identify the hub miRNAs. The expression of target gene was determined by quantitative reverse transcription‐polymerase chain reaction and Western blot. Results There were 79 and 59 differentially expressed miRNAs (DEmiRNAs) in NPSLE versus Control, and SLE versus Control, respectively. Among 35 overlapped DEmiRNAs, 5 upregulated miRNAs' (hsa‐miR‐762, hsa‐miR‐4270, hsa‐miR‐3663‐3p, hsa‐miR‐4778‐5p, and hsa‐miR‐4516) target genes were supported by at least six databases. The miRNA‐mRNA network indicated that core miRNA hsa‐miR‐762 regulated 1270 target genes. MiR‐762 was significantly upregulated in SLE and NPSLE, and over expression of miR‐762 significantly suppressed GIPC PDZ domain containing family member 3 (GIPC3) expression in SLE and NPSLE. Conclusions Upregulation of hub miRNA miR‐762 can suppress the expression of GIPC3 in both SLE and NPSLE samples, which is probably involved in the development of SLE and NPSLE. Meanwhile, along with the development from SLE to NPSLE, miR‐762 exhibits higher expression.